Design and Development of the Company Profile Website for LPK Teratai Gogakuin Indonesia as a Digital Marketing Information Platform - Dika Vivi Widyanti (Politeknik Negeri Semarang, 2025)
The advancement of digital technology has driven institutions, including vocational training centers, to adapt by utilizing online platforms for information dissemination and promotion. This study aims to design and develop a company profile website for LPK Teratai Gogakuin Indonesia to serve as a digital marketing tool and enhance the accessibility of information for the public. Using a software engineering approach comprising the stages of Requirements Planning, Design Workshop, and Implementation, the website was developed with Laravel and the MVC architecture. Key features include a welcoming message, information on activities, recruitment procedures, staff profiles, and contact details. The site’s design emphasizes responsiveness, user-friendly navigation, and visual consistency. Testing results indicate that all features function correctly, supporting the institution's goal of increasing visibility and engagement through a professional, easily accessible web presence. This website serves not only as an information portal but also as a strategic means to strengthen the institution’s brand and reach prospective learners and partners more effectively. Kemajuan teknologi digital telah mendorong lembaga, termasuk pusat pelatihan kejuruan, untuk beradaptasi dengan memanfaatkan platform daring untuk penyebaran informasi dan promosi. Penelitian ini bertujuan untuk merancang dan mengembangkan situs web profil perusahaan LPK Teratai Gogakuin Indonesia sebagai alat pemasaran digital dan meningkatkan aksesibilitas informasi bagi publik. Menggunakan pendekatan rekayasa perangkat lunak yang terdiri dari tahapan Perencanaan Persyaratan, Lokakarya Desain, dan Implementasi, situs web dikembangkan dengan Laravel dan arsitektur MVC. Fitur-fitur utama meliputi pesan sambutan, informasi tentang kegiatan, prosedur rekrutmen, profil staf, dan detail kontak. Desain situs menekankan pada responsivitas, navigasi yang ramah pengguna, dan konsistensi visual. Hasil pengujian menunjukkan bahwa semua fitur berfungsi dengan benar, mendukung tujuan lembaga untuk meningkatkan visibilitas dan keterlibatan melalui kehadiran web yang profesional dan mudah diakses. Situs web ini tidak hanya berfungsi sebagai portal informasi tetapi juga sebagai sarana strategis untuk memperkuat merek lembaga dan menjangkau calon peserta didik dan mitra secara lebih efektif..